Analysis of trends in the relationships between vehicle flow, afforestation, and noise intensity levels - Porto, Michelle Lara; Jesus, Edmir dos Santos; Pereira Junior, Antonio (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
The intensity of noise in urban centers is directly linked to the disorderly growth of cities. The objective of this research was to analyze and correlate the noise intensity levels of vehicle traffic with temperature, wind speed, vehicle flow and presence of vegetation in Bible Square. Neighborhood Cidade Nova, Maraba -PA, right bank of the Transamazônica Highway (BR 230). The methodology used was exploratory, observational, systematic, and direct. The study area was divided into three sections: A and B, separated by a central bed containing palm trees, and C, woody. In the three sections, the data were collected during sixty days (April- May 2016) in three schedules (06h30 to 07h30, 12h30 to 13h30, 18h30 to 19h30) in five points (P1, P2, P3, P4 and P5) distant between Si in forty-five meters. The data obtained indicated a tendency to increase the second variable, in the section C (r = 0.72), regarding the relationship between vehicle flow and noise intensity. In relation to tree areas (total height), data indicated that section C showed a tendency towards high noise intensity (r = 0.72); (r = 0.72), but the diameter showed a tendency of nullity (r = 0.02), that is, this variable does not interfere with the noise intensity. Therefore, the relation between the decrease in noise intensity is related to the height of the tree, because the lower the noise barrier.